Effect of Cyclophosphamide (Endoxan-Asta) on Palate Development in Albino Rats - Singh, Shamer; Sanyal, A. K.; Singh, S. P. (Indian Journal of Plastic Surgery, 1972)
Single intraperitoneal injection of varying doses of Cyclophosphamide (Endoxan-Asta) was - piven (o SE pregnant albino rats of Wistar Strain during 12th through 16th days of gestation (the day of sperm positive vaginal smear designated as zero cay of pregnancy). Ten pregnant rats were used as controls where similar amount of saline was injected without the drug. Rats were sacrificed on 21st day of gestation and foetuses removed after uterotomy and examined under the dissecting microscope for presence of any Joft palate. Highly arched palate showing defective closure was observed in most of the litters where injections were given on 12th-15th days of gestation while rats injected on 16th day of gestalion showed normal palate in all the litters. Varying degrees of actual cleftin the palate was found in 27% of foetiises trealed on 12th day. 70% in those of 13th day treatment and 429, in case of 14th day group. No cleft palate was detected in the 15th & 16th day treated foetuses or in the control ones, though the 15th day treated group showed high arched palate in 100% of the foetuses. Mechanism of the production of the developmental defect has been discussed.